Inflammatory cytokines in chronic heart failure: interleukin‐8 is associated with adverse outcome. Results from CORONA. (3rd December 2013) - Nymo, Ståle H.; Hulthe, Johannes; Ueland, Thor; McMurray, John; Wikstrand, John; Askevold, Erik T.; Yndestad, Arne; Gullestad, Lars; Aukrust, Pål
<x xml:space="preserve">Abstract</x> Aim We investigated the ability of prototypical inflammatory cytokines to predict clinical outcomes in a large population of patients with chronic systolic heart failure (HF). Methods and results Serum levels of tumour necrosis factor‐α (TNF‐α), soluble TNF receptors type I and II (sTNF‐RI and sTNF‐RII), and the chemokines monocyte chemoattractant protein‐1 (MCP‐1) and interleukin‐8 (IL‐8) were analysed in 1464 patients with chronic ischaemic systolic HF in the CORONA study, aged ≥ 60 years, in NYHA class II–IV, and related to the primary endpoint (n = 320), as well as any coronary event (n = 255), all‐cause mortality (n = 329), cardiovascular (CV) mortality (n = 268), and the composite endpoint hospitalization from worsening heart failure (WHF) or CV mortality (n = 547). TNF‐α, sTNF‐RI, sTNF‐RII, and IL‐8, but not MCP‐1, were independent predictors of all endpoints except the coronary endpoint in multivariable models including conventional clinical variables. After further adjustment for estimated glomerular filtration rate, the ApoB/ApoA‐1 ratio, NT‐proBNP, and high‐sensitivity C‐reactive protein, only IL‐8 remained a significant predictor of all endpoints (except the coronary endpoint), while sTNF‐ RI remained independently associated with CV mortality. Adding IL‐8 to the full model led to a significant improvement in net reclassification for all‐cause mortality and CV hospitalization, but only a borderline significant improvement for the primary endpoint, CV mortality, and the composite endpoint WHF hospitalization or CV mortality. Conclusion Our study supports a relationship between IL‐8 and outcomes in patients with chronic HF. However, the clinical usefulness of IL‐8 as a biomarker in an unselected HF population is at present unclear.